2015
DOI: 10.1148/radiol.14140847
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast-enhanced MR Imaging Curve-type Analysis: Is It Helpful in the Differentiation of Prostate Cancer from Healthy Peripheral Zone?

Abstract: Qualitative DCE MR imaging time-curve-type analysis performs poorly for differentiation of PCa from healthy prostatic tissue. Interobserver agreement is excellent in assessment of type 3 curves but only moderate for type 1 and 2 curves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 39 publications
2
53
1
11
Order By: Relevance
“…The binary results of DCE lead to good Total 5 49 24 78 Total 2 55 23 80 interreader agreement; however, the accuracy of DCE is only 69-70% for both scales and both readers. These results are similar to those of a previous report of ESUR PI-RADS 32 and are in line with other publications that evaluated the accuracy of DCE for prostate cancer detection. [33][34][35] Our study found no clear difference in the accuracy of overall scores, for both readers, using a cut-off value of 3 or 4.…”
Section: Discussionsupporting
confidence: 92%
“…The binary results of DCE lead to good Total 5 49 24 78 Total 2 55 23 80 interreader agreement; however, the accuracy of DCE is only 69-70% for both scales and both readers. These results are similar to those of a previous report of ESUR PI-RADS 32 and are in line with other publications that evaluated the accuracy of DCE for prostate cancer detection. [33][34][35] Our study found no clear difference in the accuracy of overall scores, for both readers, using a cut-off value of 3 or 4.…”
Section: Discussionsupporting
confidence: 92%
“…Sinyal intensitesi değişikliklerinin kalitatif analizi, sinyal intensitesi -zaman eğrisi, kantitatif analiz ise kontrast madde konsantrasyonzaman eğrileri ya da fizyolojik farmakokinetik parametreler değerlendirilerek yapılabilir [12].…”
Section: Dk-mrg Analiz Yöntemleriunclassified
“…In fact, a meta-analysis failed to find a significant difference between visual and nonvisual analysis, 35 and a recent study showed poor performance of curve type analysis in detection of prostate cancer. 36 Quantitative parameters can also be calculated from DCE-derived pharmacokinetic maps. Typical parameters include: k trans , representing forward transfer of the contrast agent from vasculature to the interstitial space; K ep , representing backward leakage of contrast from interstitial space to vasculature; and v e , fractional volume of the interstitial space per tissue volume.…”
Section: Dcementioning
confidence: 99%